Effect of different physical factors on the synthesis of spherical gold nanoparticles towards cost‐effective biomedical applications - Zahra Bahmanyar; Fatemeh Mohammadi; Ahmad Gholami; Mehdi Khoshneviszadeh (IET Nanobiotechnology)
Abstract Gold nanoparticles (AuNPs) have great potential to contribute to numerous application fields of biomedicine, which are highly dependent on their physicochemical properties, such as size and shape. Due to the final characteristics, nanoparticles (NPs) are primarily affected by different factors of reaction conditions; the present study aimed to evaluate the effects of manipulating the main physical parameters of the Turkevich method to optimise the fabrication of citrated capped AuNPs in a spherical shape, desirable final size, and efficiency. For this purpose, various experiments of citrate‐capped spherical AuNPs synthesis were designed to study the roles of a wide range of initial pH values and temperature of reaction, Na3Cit/HAuCl4 molar ratio, and two order reagent additions, method I and method II, in the final characterisations and reaction efficacy. Prepared NPs synthesised with different experiments were characterised by dynamic light scattering, UV‐Visible, and fourier transform infrared spectroscopy. Furthermore, NPs obtained from optimised synthesis conditions were more detailed using UV‐Visible, transmission electron microscopy, and XRD. The findings indicated that the final size and synthesis efficacy of citrated capped spherical AuNPs were significantly affected by all studied synthesis parameters and the order addition of reagents. The higher initial reaction temperature and Na3Cit/HAuCl4 Molar ratio provided a smaller particle size with desirable synthesis efficacy. Besides, final optimised NPs were provided in cubic crystal structures, and each NP's single crystal was obtained. In sum, our findings indicated that optimising synthesis conditions could improve size distribution, morphology, crystallite size, and structures of final NPS, as well as efficiency, which is a principal factor associated with future cost‐effective productions on large scales. Further studies are needed in this regard.